Investigation of coal bottom ash and fly ash in concrete as replacement for sand and cement - Rafieizonooz, M. (Elsevier Ltd, 2016)
Malaysia produces about 8.5 million tons of coal ash as waste which comprises of bottom ash and fly ash. Reusing such waste which is otherwise sent to landfills is an environment-friendly option. Hence, the major aim of this research study was to investigate their use in concrete to replace sand with bottom ash waste and cement with fly ash. Concrete specimens were prepared incorporating 0, 20, 50, 75 and 100% of bottom ash replacing sand and 20% of coal fly ash by mass, as a substitute for Ordinary Portland cement. Fresh and hardened state properties of the experimental specimens were determined. Results revealed that concrete workability reduced when bottom ash content increased replacing sand. On the other hand, at the early age of 28 d, no significant effect was observed in compressive, flexural and tensile strengths of all concrete samples. After curing at 91 and 180 d ages, compressive strength of both the experimental and control concrete samples increased significantly but remained almost similar. However, flexural and splitting tensile strengths of the experimental mix containing 75% bottom ash and 20% fly ash exceeded much more than the control sample. Moreover, drying-shrinkage of experimental concrete mixtures containing 50%, 75% and 100% bottom ash and 20% fly ash was lower than the control mix. It is concluded that those experimental concrete mixes can be used in several structures (foundations, sub-bases, pavements, etc.) which will minimize the cost, energy and environmental problems to a great extent.